2003
DOI: 10.1021/ie020361i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibrous Bed Permeability on Steady-State Coalescence

Abstract: The effect of fibrous bed permeability on the efficiency of steady-state coalescence was investigated. Bed permeability was changed by compression of polyurethane fibers. The effect of bed permeability was followed based on the effluent oil concentration and critical velocity. An oil-in-water system was used as the model of unstable emulsion, with the drop size smaller than the pore size of the fibrous bed in all experiments. Different fluid velocities, bed lengths, and fluid-flow orientations were applied. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Hence, it would be necessary to determine the value of the bed critical permeability for each material and work with a bed of higher permeability to obtain optimal separation conditions. 8 Velocities The oil concentration in the effluent was determined by IR spectrometry from a carbon tetrachloride extract, after addition of HCl to obtain pH 2, to stabilize the oily water samples.…”
Section: Equipment and Operating Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it would be necessary to determine the value of the bed critical permeability for each material and work with a bed of higher permeability to obtain optimal separation conditions. 8 Velocities The oil concentration in the effluent was determined by IR spectrometry from a carbon tetrachloride extract, after addition of HCl to obtain pH 2, to stabilize the oily water samples.…”
Section: Equipment and Operating Proceduresmentioning
confidence: 99%
“…The critical velocity was determined from the exponential dependence of the effluent oil concentration on the fluid velocity, in each particular experiment. In our studies, the critical velocity (v k15 ) 8 is the fluid velocity determined at a point when the effluent oil concentration reaches 15 mg L -1 , this concentration often being quoted as the tolerable level in oily water. As the working velocity is a crucial factor for equipment size and capital costs, the goal of optimization is to find the conditions corresponding to its maximum, which must be below the critical velocity.…”
Section: Properties Of the Fibrous Materials And Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches have shown that coalescer is effective in reducing high levels of oil and grease in appropriate particle size range that achieve technically and economically efficient oil-water separation [7][8][9]. Oil droplets are captured by the solid medium, forming oil films on the surfaces during the coalescence process; then the stable oil emulsions are demulsified upon continued growth of the collected oil droplets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Coalescers are basically improved filtration systems using designed filtration medium, usually modified polymeric resins, which destabilize emulsion and accelerate the coalescence of dispersed oil droplets and provide high adsorption capacity and oil-removal efficiency [24]. These characteristics are important due to hydrogen bonding between oil molecules and the free hydrophobic part of the fixed surfactant.…”
Section: Introductionmentioning
confidence: 99%